(untitled) (Third Sector Social Economic Review, 2022)
In this study, it is aimed to investigate the theoretical and empirical literature in the light of discussions on the trilemma and the dilemma. The trilemma hypothesis predicts that the objectives of monetary independence, freedom of capital movements and exchange rate stability cannot be implemented simultaneously, but only two of them can be achieved. According to this view, under financial integration monetary policy independence may be obtained through a floating exchange rate regime. However the dilemma hypothesis developed by Rey (2015) argues that under financial globalization, the monetary policies of the center countries affect the national monetary policies of the peripheral countries, so these countries cannot implement an independent monetary policy regardless of the exchange rate regime. According to this view, the exchange rate no longer acts as a shock absorber in increasingly globalized markets, so even countries with flexible exchange rates cannot implement independent monetary policy. Therefore in recent years many economists have begun to argue that the trilemma has evolved into a dilemma. When the discussions and empirical studies in the literature are examined, on the one hand, there are findings and opinions that the trilemma is still valid, on the other hand, there are criticisms and findings that the trilemma has turned into a dilemma. There are also findings showing that the dilemma is partially valid.